DAMPAK BURNOUT PADA TENAGA KESEHATAN: TINJAUAN LITERATUR TENTANG FAKTOR PENCETUS DAN STRATEGI PENCEGAHAN - Ni Putu Swastini; Winda Trijayanthi Utama (CV. Jasa Sukses Abadi, 2026)
Burnout is a common work-related stress syndrome among healthcare workers, characterized by emotional exhaustion, depersonalization, and reduced professional achievement. This condition has a negative impact on service quality, worker health, and patient safety. Factors contributing to burnout include personal characteristics, sociodemographic factors, work environment conditions, high workload, and lack of organizational support. This study aims to review the literature on the factors that trigger burnout in healthcare workers and effective prevention strategies at the individual and organizational levels. The study used a literature review design with a search of articles in the PubMed, ScienceDirect, and Google Scholar databases using the keywords “burnout,” “healthcare workers,” “risk factors,” and “prevention strategies.” The articles included were publications from the last ten years, in Indonesian and English, and relevant to the research objectives. Data were synthesized narratively to identify risk factors and prevention strategies for burnout. Factors contributing to burnout included individual factors (age, gender, personality type), working conditions (high workload, overtime, interaction with patients), and organizational environment (managerial support, work culture). Effective prevention strategies combine individual interventions, such as mindfulness, CBT, and coping training, with organizational interventions, including supportive leadership, flexible policies, open communication, and empowerment of healthcare workers. Preventing burnout in healthcare workers requires a holistic approach that integrates individual and organizational strategies. Management and leadership support that emphasizes employee well-being is key to reducing burnout and improving the quality of healthcare services.